(untitled) (Medico Legal Update, 2021)
Introduction: During pregnancy maternal thyroid dysfunction has been associated with a number of adverse outcomes, like preterm birth, placental abruption, fetal death and impaired neurological development in the child. The presence of Thyroid Peroxidase Antibody (TPO-Ab) results miscarriage, preterm birth and maternal post-partum thyroid disease. Hypothyroidism is closely associated with the presence of Thyroid Peroxidase Antibody. If a pregnant woman is positive for TPO-Ab in early pregnancy, her chances to developing thyroid abnormalities. Objective: To find out the level of TPO-Ab and thyroid status in first trimester of pregnancy. Method: Observational cross-sectional Study was designed in Department of Biochemistry, Medical college, Vadodara, Gujarat, India. Sample Size: 200 Normal pregnant women that randomly selected from the first trimesters of pregnancy. The study parameters were - thyroid peroxidase anti-body (TPO-Ab); serum thyroid stimulating hormone (TSH); serum T3 and serum T4. Result: Our study found that 30(15%) pregnant women of first trimester was hypothyroidism (TSH >2.5mIU/l) Out of these 30 females, 9(4.5%) had overt hypothyroidism & 21 (10.5%) had subclinical hypothyroidism, among these 30 subjects, 26(13%) had found TPO-Ab positive (TPO-Ab >35 IU//mL) there was a significant positive correlation between positive TPO-Ab and serum TSH level of study subjects and there was a negative correlation between serum TSH and serum T4,T3 level in study subjects. Conclusion: In this study we found 15% prevalence of hypothyroidism (4.5 % overt & 10.5 % subclinical) in first trimester of pregnancy. We found positive TPO-Ab in 13% of pregnant females and all these had some thyroid dysfunctions, subclinical or overt hypothyroidism, subclinical being much more common than overt hypothyroidism.